"Just" don’t ask: Exclusives and potential questions - Warstadt, Alex (Proceedings of Sinn und Bedeutung, 2020)
The English exclusive just is not synonymous with other exclusives such as only in sentences like Sometimes, bad things just/only happen. I give a new analysis of just which explains this and other puzzling readings of just observed in earlier work (e.g. Wiegand, 2016; Beltrama, 2018). I argue that just excludes alternatives derived from a potential question, or possible future QUD, in the sense of Onea (2016). This new perspective makes it possible to give the first unified account of these non-canonical exclusive readings of just, and provides evidence that the semantics of lexical items can be sensitive to possible futures of the discourse.